PROFIL DISPOSISI BERPIKIR KRITIS MAHASISWA PENDIDIKAN BIOLOGI DI PERGURUAN TINGGI - Syahfitri, Jayanti; Firman, Harry; Redjeki, Sri; Sriyati, Siti (Jurnal BIOEDUIN, 2019)
Critical thinking disposition is an important component in determining a person's critical thinking abilities. This study aims to see a comparison of the score critical thinking disposition of biology education students at University of Muhammadiyah Â Bengkulu which was involving 73 students taken from 38 (52.05%) of Biology Education students in the 1st year and 35 (47.95%) are students in the 2nd year. The instrument used in this study is a Critical Thinking Disposition Test in Biology consisting of 10 questions for each indicator of critical thinking disposition. The results indicate that profile of critical thinking disposition in Biology Education students in the 2nd year is higher than students in 1st year. Profile of critical thinking disposition of Biology Education students in the 2nd year is dominated in the medium category for indicators of Â truth-seeking, systematicity, self-confidence, inquisitiveness, and maturity. And on the indicators of open-mind and analyticity are shows as high profile of disposition. While profile of critical thinking disposition disposition in Biology Education students in the 1st year is dominated in the low category, namely on the indicators of truth-seeking, analyticity, systematicity, inquisitiveness, and maturity. Only on the indicators of open-mind which is interpreted as a high profile of critical thinking disposition and in medium category for self confidence